A modified salp swarm algorithm (SSA) combined with a chaotic coupled map lattices (CML) approach for the secured encryption and compression of medical images during data transmission. (April 2021) - Thirumarai Selvi, C.; Amudha, J.; Sudhakar, R.
Highlights: Medical image data is the important data as medical systems to analyze patient's health record. The medical images should be encrypted and transmitted safely over the insecure network. In this paper, a combined coupled map lattice (CML) with modified algorithm of salp swarm (SSA) is proposed. The modified SSA with whale optimization algorithm (WOA) is applied to reduce the computational time. The experimental outcome shows the proposed method is efficient to encrypt the image. Abstract: Medical image data analysis is a significant data in medical systems to analyze patient's health record. The biomedical image processing techniques and modernization of image devices are enhancing the medical image data. The main advantages of medical imaging data are (i) the medical imaging data are transmitted in the secure network in safe from the hackers (ii) medical imaging data can be shared quickly and easily between health care providers and departments. The chaotic system based different encryption algorithms using researches is analyzed. There are numerous issues in transmission of image such as weak security, small key space and high computational time. In this manuscript, a combined coupled map lattice (CML) with modified salp swarm algorithm is proposed. This algorithm compresses and encrypts the image using coupled map lattice (CML). This CML initially generates the number of encrypted images in modified SSA population. After the initialization, the modified SSA with whale optimization algorithm (WOA) is applied to reduce the computational time and maximize entropy in image cipher. To enhance the security of medical image is encrypted as a cipher image and transmits over the network. The experimental outcomes demonstrate that the proposed technique is more efficient to encrypt the medical image and has capability to resist the different distinct attacks.